Microstructures and mechanical properties of a 30CrNi2MoV steel/GH4098 joint produced by hot-compression bonding - Shengqing Wu; Sheng Liu; Hexin Wang; Shaofei Ren; Bin Xu; Xiaopeng Zhang; Mingyue Sun (Materials & Design)
This study elucidates the microstructures and mechanical properties of a 30CrNi2MoV steel/GH4098 joint produced via hot-compression bonding (HCB). Owing to the mutual diffusion of GH4098 and 30CrNi2MoV, the bonding interface becomes an interface band where Al2O3/Ti(C, N) is distributed on the side near GH4098 and Ti(C, N)/M23C6 is distributed on the side near 30CrNi2MoV. A transition layer occurs between the interface band and 30CrNi2MoV due to the diffusion of austenite stabilization elements dominated by Ni from GH4098 to 30CrNi2MoV. As the hot compression temperature increases, oxides and carbides are thermally dissolved into the matrix and Al2O3 transitions from its δ phase to α phase. As the strain increases, the bonding interface bugles and the interfacial oxide layer is destroyed. The highest interfacial bonding strength is obtained under conditions associated with high temperatures and large deformation.